2011
DOI: 10.1016/j.jecp.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating challenge reactivity from psychomotor activity in studies of children’s psychophysiology: Considerations for theory and measurement

Abstract: Current methods of assessing children’s physiologic “stress reactivity” may be confounded by psychomotor activity, biasing estimates of the relation between reactivity and health. We examine the joint and independent contributions of psychomotor activity and challenge reactivity during a protocol for children ages 5–6 (N=338). Measures of parasympathetic (RSA) and sympathetic (PEP) reactivity were calculated for social, cognitive, sensory, and emotional challenge tasks. Reactivity was calculated relative to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 57 publications
3
77
1
Order By: Relevance
“…Given the novelty of the present statistical modeling approach, we excluded dyads that had missing RSA data for any single 30-second epoch during the joint puzzle task. This conservative approach was taken to reduce the likelihood of spurious results related to patterns of missing data, as ECG data is often unable to be processed during a given epoch due to movement-related artifact by the participant, also reducing the potential influence of motor activity on changes in RSA (e.g., Bush et al, 2011). As such, continuous RSA data throughout the task was available for a total of 79 mother-child dyads, split into groups of CM (n=43) and non-CM (n=36) families.…”
Section: Methodsmentioning
confidence: 99%
“…Given the novelty of the present statistical modeling approach, we excluded dyads that had missing RSA data for any single 30-second epoch during the joint puzzle task. This conservative approach was taken to reduce the likelihood of spurious results related to patterns of missing data, as ECG data is often unable to be processed during a given epoch due to movement-related artifact by the participant, also reducing the potential influence of motor activity on changes in RSA (e.g., Bush et al, 2011). As such, continuous RSA data throughout the task was available for a total of 79 mother-child dyads, split into groups of CM (n=43) and non-CM (n=36) families.…”
Section: Methodsmentioning
confidence: 99%
“…Both task demands and environmental stimuli, such as visual images, temperatures, sounds and smells, have an effect on the way children process incoming information (e.g., Bush, Alkon, Obradovic, Stamperdahl, & Boyce, 2011;McManis, Bradley, Berg, Cuthbert, & Lang, 2001;Sharp, van Goozen, & Goodyer, 2006;Schell & Crone, 2013;Tottenham, Hare, & Casey, 2011). Environmental stimuli including emotionally loaded stimuli, also referred to as affective stimuli, may capture and divert attention regardless of their relevance to ongoing tasks (Dolcos & McCarthy, 2006), affecting children's cognitive control processes (Tottenham et al, 2011;Schell & Crone, 2013) and eliciting a range of subjective and autonomic responses (McManis et al, 2001;Shapiro, Sgan Cohen, Parush, & Melmed, 2009;Sharp et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The consensus is that these may constitute reasonable reference points for assessing reactivity depending on the comparison condition. Previous experiments from our lab within a sample of 5 year olds 38 suggest that the psychomotor activity elicited by the movement-inhibiting baseline condition ( e.g., talking, social engagement, gesturing) is an important consideration; findings suggested that the use of social engagement to keep children calm and focused, such as reading a story, is an appropriate baseline comparison for social challenges whereas neutral videos may be appropriate as comparison values for reactivity to arousing videos for children. Attending to a video is associated with increased attention and it has a calming response in both branches of the ANS.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol includes a second lullaby in order to offset this possibility, although its occurrence immediately following challenges may also lead to carryover effects. Limited ability to assess "true" resting conditions is a long-standing challenge for ANS researchers working with young children 38 . More generally, assessing toddlers is challenging at times and requires occasional modification of procedures (such as stopping to change a diaper or allowing a child to hold their small soft toy to prevent a tantrum that would prohibit continuation of the assessment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation